“Islam Datang dan Menetap di Thailand” - Marissa Grace Haque; Nelmida Nelmida; Vidiyanna Rizal Putri; Denok Sunarsi; Rr Vemmi Kesuma Dewi (South Sulawesi Education Develoment (SSED), 2019)
The Kingdom of Thailand is one of the countries in Southeast Asia with a majority Buddhist Trevada population, but with its open character it is able to accept Islam and give its adherents the freedom to develop. The arrival of Islam for the first time in the Kingdom of Thailand in the city of Ayutthai, leaving a trail of evidence of its presence until now has grown along with the entry of other Muslims from overseas. Even though there has been upheaval in the South because of the forced history, in general the social life of the Muslim community in Thailand is currently in a conducive condition. This study uses a naturalistic qualitative approach.